Endoscopy-related musculoskeletal injuries in gastroenterology fellows - Villa, Edward; Attar, Bashar; Trick, William; Kotwal, Vikram (Endoscopy International Open, 2019)
Background and study aims Gastroenterologists are at high risk for work-related musculoskeletal injuries. Studies have shown that 37 % to 89 % of endoscopists have work-related musculoskeletal injuries. While all surveys until now have focused on practicing endoscopists, there have been no publications assessing the prevalence of musculoskeletal injuries among gastrointerology fellows, which we sought to investigate.Methods A 22-question survey about ergonomics and work-related musculoskeletal injuries was sent to 114 gastroenterology fellows in different programs across the United States in June 2016, and an additional 103 surveys were distributed at Digestive Disease Week in May 2017. Responses were collected, and data were analyzed.Results A total of 156 surveys were collected. Of these, 74 fellows (47 %) reported a new musculoskeletal injury related to endoscopy. Injuries occurred mostly in the first year of fellowship (85 %, P < 0.001). The most common sites of injury were the right wrist (53 %), left thumb (42 %), back (27 %), and neck (22 %). Only 26 % those who had endoscopy-related musculoskeletal injuries had received training in ergonomics compared to 45 % of those who did not have injury (P = 0.012), and ergonomics training was highly desirable among respondents, particularly among those with previous injuries (P = 0.0030)Conclusion Musculoskeletal injuries related to endoscopy are very common among gastroenterology fellows, particularly during the first year of fellowship. While the overall percentage of fellows who received training in ergonomics was low, those who did receive training were less like to report a musculoskeletal injury. There is an urgent need for ergonomics training among Gastroenterology fellows.